The Diversity That We Love. Commodification and Control of Diversity in Gentrifying Neighbourhoods - Bolzoni, Magda (Italian Sociological Review, 2022)
In a time of growing appreciation for urban diversity, consuming ethnic food, sharing the streets with foreign people and showing interest for cultural diversity often operate as a means of social distinction, in particular among the new urban middle classes. Hence, culturally and ethnically diverse atmosphere have come to be considered as an asset for urban branding and neighbourhoods’ regeneration. The implications for those who embody such diversity, however, are often unclear. The paper addresses the ambiguous relationship between diversity and urban upgrading, focusing on the case of Turin and, more specifically, on a mixed neighbourhood that after a period of misfortune has become one of the new trendy spots of the city, also building on its diverse and gritty atmosphere. Bringing together literature on gentrification and social mix, commodification of diversity in urban transformations, and everyday multiculturalism, the paper offers an analysis of practices of negotiation, control and commodification of diversity in different domains of neighbourhood’s life: commercial landscape, public spaces and neighbourhoods’ representations. It argues that middle classes’ love for diversity often appears related to the ability to control it, to decide which kind of diversity is ‘good’ and should be visible and displayed in the neighbourhood space. In this frame, diversity may become a particular kind of commodity, to be consumed in a safe and sanitized environment and the apprec